Who may benefit from prophylactic cranial irradiation amongst stage III non-small cell lung cancer patients? - (:unkn) unknown (ZERBINIS MEDICAL PUBL, 2013)
Purpose: To identify a high risk group of non-small cell lung cancer (NSCLC) patients who may benefit from preventive strategies in order to reduce the rate of brain metastasis. Methods: Two-hundred stage IIIA (47.5%) and IIIB (52.5%) NSCLC patients were analysed (median age 61 years, range 29-82). Pathological diagnosis consisted of 27% adeno carcinomas, 48.5% squamous cell carcinomas, and 24.5% non-small cell lung carcinomas. Brain metastasis rate was calculated and compared in relation to age, gender, stage, histology, chemotherapy and surgery. Results: Median follow-up was 15 months (range 2-65), and the 2-year survival rate was 35%. Two-year incidence of brain metastasis was 23%. In univariate analysis, 32.9% of the patients younger than 60 years of age developed brain metastasis, in contrast to 15.3% of those older than 60 years (p=0.003). Brain was the first metastatic site in younger patients (44.4%) which was significantly higher than in the older age group (23%) (p=0.03). Adenocarcinoma had higher risk (39.6%) than squamous cell carcinoma (15.7%) for brain metastasis (p<0.0001). Patients 60 years old or younger with adeno carcinoma (53.3%) had higher risk for brain metastasis than all the others (18%; p<0.0001). Conclusion: In locally advanced NSCLC patients, age and adenocarcinoma histology represent high risk factors for early development of brain metastasis. Many of the failures are isolated brain lesions and future studies are required to assess the benefit of preventive strategies in selected patients.
Keywords: brain metastasis; non-small cell lung cancer; prophylactic cranial irradiation; SOUTHWEST-ONCOLOGY-GROUP; MULTICENTER RANDOMIZED-TRIAL; TERM-FOLLOW-UP; BRAIN METASTASES; PHASE-II; PREOPERATIVE CHEMOTHERAPY; NEOADJUVANT CHEMOTHERAPY; MULTIMODALITY TREATMENT; FAILURE PATTERNS; GROUP RTOG